Lexical Predictors of Intelligibility in Young Children's Speech. - Mahr, Tristan J.; Hustad, Katherine C. (Journal of Speech, Language & Hearing Research)
Purpose: Speech perception is a probabilistic process, integrating bottom-up and top-down sources of information, and the frequency and phonological neighborhood of a word can predict how well it is perceived. In addition to asking how intelligible speakers are, it is important to ask how intelligible individual words are. We examined whether lexical features of words influenced intelligibility in young children. In particular, we applied the neighborhood activation model, which posits that a word's frequency and the overall frequency of a word's phonological competitors jointly affect the intelligibility of a word. Method: We measured the intelligibility of 165 children between 30 and 47 months in age on 38 different single words. We performed an item response analysis using generalized mixed-effects logistic regression, adding word-level characteristics (target frequency, neighborhood competition, motor complexity, and phonotactic probability) as predictors of intelligibility. Results: There was considerable variation among the words and the children, but between-word variability was larger in magnitude than between-child variability. There was a clear positive effect of target word frequency and a negative effect of neighborhood competition. We did not find a clear negative effect of motor complexity, and phonotactic probability did not have any effect on intelligibility. Conclusion: Word frequency and neighborhood competition both had an effect on intelligibility in young children's speech, so listener expectations are an important factor in the selection of items for children's intelligibility assessment.